Pemodelan Implementasi Cost Down Blasting Melalui Daur Ulang Limbah Solar Dan Oli Bekas Dengan Pendekatan Metode 5 WHY Analisis dan Simulasi Sistem Dinamis - Sakti, Yuni Krida (Fakultas Teknik Universitas Islam Makassar, 2025)
Blasting in mining is intended to break large rocks into smaller sizes for easier transport to processing facilities. However, high blasting costs have become a major issue at PT. X, a coal mining company. A significant portion of these costs is due to the annual consumption of approximately 200,000 liters of pure diesel for ANFO mixing, amounting to IDR 1.8 billion. This study aims to analyze the root cause of high blasting costs using the 5 Why Analysis method and forecast potential cost reductions over the next 12 months using system dynamics simulation. The primary cause identified is the full reliance on pure diesel for ANFO mixing. As a corrective strategy, a Cost Down Blasting approach is proposed by utilizing recycled diesel and used hydraulic oil in the ANFO mix. Simulation results show that blasting costs could be reduced by around IDR 500 million, or approximately 28%, with pure diesel consumption reduced to 141,689 liters. In addition, the use of recycled diesel and oil could increase to 56,137 liters, compared to only 22,396 liters in the previous year.